Power and democracy in Iceland: An Introduction - Guðmundur Heiðar Frímannsson (Veftímaritið Stjórnmál og stjórnsýsla, 2018)
From the article: This research project which results are presented in this special issue of Icelandic Review of Politics and Administrations has been going on since 2014. It has resulted in various theoretical articles published earlier. This special issue is not a final report of an investigation into power and democracy in Iceland as has been published in other Nordic countries. The funds received for this project were more limited than political scientists received in other Nordic countries to conduct similar investigations of their own governing structures. The results are varied and do not form a coherent whole but they are interesting in their own right. This special issue marks the ultimate point in the research. All the articles engage with various features of Icelandic democracy, be it the machinery of state, Icelandic power structure, political parties or the changing social background of the citizens and their relations to the Icelandic state.